An historical and critical reconstruction of disciplines and interdisciplinarity in urban studies - Pizzo, Barbara; Gribat, Nina; Höhne, Stefan; Michel, Boris; Schuster, Nina (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2019)
The paper offers a reconstruction of the origins of disciplines particularly in German-speaking countries, through the contributions of Jacob Christoph Burckhardt, Friedrich Engels, George Simmel, Camillo Sitte, Max Weber, just to name a few, and the way in which their work shaped cultures and systematizations of knowledge. Using a dialogical form, scholars with different education discuss how and when different interests and stream of researches crystallized into disciplines, and how and when they have approached or moved away from each other over time depending on the predominance of questions or problems, but also in relation with changes in the political context or even for ideological reasons.